Adaptive regulation of the ileal apical sodium dependent bile acid transporter (ASBT) in patients with obstructive cholestasis. Issue 3 (8th September 2005) - Hruz, P; Zimmermann, C; Gutmann, H; Degen, L; Beuers, U; Terracciano, L; Drewe, J; Beglinger, C
Abstract : Background/aims: The apical sodium dependent bile acid transporter ASBT (SLC10A2) contributes substantially to the enterohepatic circulation of bile acids by their reabsorption from the intestine. In the rat, its adaptive regulation was observed in the kidneys, cholangiocytes, and terminal ileum after bile duct ligation. Whether adaptive regulation of the human intestinal ASBT exists during obstructive cholestasis is not known. Methods: Human ASBT mRNA expression along the intestinal tract was analysed by real time polymerase chain reaction in biopsies of 14 control subjects undergoing both gastroscopy and colonoscopy. Their duodenal ASBT mRNA expression was compared with 20 patients with obstructive cholestasis. Additionally, in four patients with obstructive cholestasis, duodenal ASBT mRNA expression was measured after reconstitution of bile flow. Results: Normalised ASBT expression in control subjects was highest (mean arbitrary units (SEM)) in the terminal ileum (1010 (330)). Low ASBT expression was found in colonic segments (8.3 (5), 4.9 (0.9), 4.8 (1.7), and 1.1 (0.2) in the ascending, transverse, descending, and sigmoid colon, respectively). Duodenal ASBT expression in control subjects (171.8 (20.3)) was found to be approximately fourfold higher compared with patients with obstructive cholestasis (37.9 (6.5); p<0.0001). Individual ASBT mRNA expression was inversely correlated with bile acid and bilirubin plasma concentrations. In four cholestatic patients, average ASBT mRNA increased from 76 (18) before to 113 (18) after relief of cholestasis (NS). Immunohistochemical assessment indicated that ASBT protein was expressed on the apical surface of duodenal epithelial cells. Conclusion: Obstructive cholestasis in humans leads to downregulation of ASBT mRNA expression in the distal part of the human duodenum.